Hydrothermal Fields In Oceanic Fracture Zone Settings: An Example From The Blanco F.Z., Northeast Pacific - James R. Hein (International Marine Minerals Society, 2001)
Low- to intermediate-temperature, diffuse-flow hydrothermal fields and associated mineral precipitates have been found at many locations along oceanic spreading centers, back-arc basin spreading axes, and midplate hot-spots. However, this type of hydrothermal field has not been found in oceanic fracture zones until recently. We mapped and collected samples from an active hydrothermal field in the Blanco Fracture Zone (BFZ) located in the northeast Pacific. The BFZ connects the Gorda and Juan de Fuca spreading centers and is divided into east and west segments by Cascadia Depression, a small spreading center. Small pull-apart basins occur along both the east and west segments. A complex set of basins near the western end of the BFZ includes from east to west, Surveyor Depression, East Blanco Depression (EBD), and West Blanco Depression. The hydrothermal field described here is located in the EBD.